2008
DOI: 10.1080/09512740802294697
|View full text |Cite
|
Sign up to set email alerts
|

Fighting irrelevance: an economic community ‘with ASEAN characteristics’1

Abstract: Contrary to expectations at the time, the financial crises of 1997-98 may have strengthened ASEAN. The backlash against a perceived unsympathetic Western response put ASEAN at center stage in new regional cooperative arrangements. Moreover, the rivalry between China and Japan for regional leadership has led them both to seek to negotiate regional partnerships with ASEAN as a whole. ASEAN, however, faces new challenges -particularly from rapid economic growth in China and India, and from the proliferation of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…65 Mounting rivalry can be seen as a source for structural change in this context. 66 There are other examples of intense rivalry that can be quoted to underline the argument made here. The Mekong River region is one such instance.…”
Section: Competitionmentioning
confidence: 88%
“…65 Mounting rivalry can be seen as a source for structural change in this context. 66 There are other examples of intense rivalry that can be quoted to underline the argument made here. The Mekong River region is one such instance.…”
Section: Competitionmentioning
confidence: 88%
“…Its inability to cope with the crisis was due to a lack of instruments for dealing with economic and political consequences [10] [11]. In the meantime, China's accession to the WTO and the rise of emerging markets, particularly the BRIC (Brazil, Russia, India, China and South Africa), forced ASEAN members to cooperate so that the region would continue to attract businesses and investors.…”
Section: Asean's New Life Under the Aecmentioning
confidence: 99%
“…He also points out that these obstacles are a result of government application and implementation rather than policies [29]. Consequently, ASEAN-X has "the potential to institutionalize a multi-tier ASEAN characterized by fragmented integration" [30].…”
Section: Inherent Problems Within Aseanmentioning
confidence: 99%
“…In a more recent study, Ravenhill (2008) suggested that the financial crisis of 1997-1998 may have strengthened ASEAN member countries. Apart from that, the rivalry between China and Japan for regional leadership led them to seek negotiations with ASEAN.…”
Section: Literature Reviewmentioning
confidence: 99%